Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 192957 by York12 last updated on 31/May/23

  bx^3 =10a^2 bx + 3a^3 y , ay^3 = 10ab^2 y + 3b^3 x  solve for x and y in terms of (a , b)  and solve for a and b in terms of  (x , y )

$$ \\ $$$${bx}^{\mathrm{3}} =\mathrm{10}{a}^{\mathrm{2}} {bx}\:+\:\mathrm{3}{a}^{\mathrm{3}} {y}\:,\:{ay}^{\mathrm{3}} =\:\mathrm{10}{ab}^{\mathrm{2}} {y}\:+\:\mathrm{3}{b}^{\mathrm{3}} {x} \\ $$$${solve}\:{for}\:{x}\:{and}\:{y}\:{in}\:{terms}\:{of}\:\left({a}\:,\:{b}\right) \\ $$$${and}\:{solve}\:{for}\:{a}\:{and}\:{b}\:{in}\:{terms}\:{of}\:\:\left({x}\:,\:{y}\:\right) \\ $$

Commented by York12 last updated on 02/Jun/23

Commented by York12 last updated on 02/Jun/23

no common roots  means no existence for any value  of x which can satify both equations  ⇒ your system of  equations is again  wrong

$${no}\:{common}\:{roots} \\ $$$${means}\:{no}\:{existence}\:{for}\:{any}\:{value} \\ $$$${of}\:{x}\:{which}\:{can}\:{satify}\:{both}\:{equations} \\ $$$$\Rightarrow\:{your}\:{system}\:{of}\:\:{equations}\:{is}\:{again} \\ $$$${wrong}\: \\ $$

Answered by a.lgnaoui last updated on 01/Jun/23

 { ((bx^3 −10a^2 bx=3a^3 y⇒   y=((xb(x^2 −10a^2 ))/(3a^3 )) (1))),((3b^3 x=ay^3 −10ab^2 y⇒  x=((ya(y^2 −10b^2 ))/(3b^3 ))  (2))) :}  y^2 =((x^2 b^2 (x^2 −10a^2 )^2 )/(9a^6 ))  x^2 =((y^2 a^2 (y^2 −10b^2 ))/(9b^6 ))  (1)⇔y=(b/(3a^3 ))[((ya(y^2 −10b^2 )/(3b^3 ))][(((y^2 a^2 (y^2 −10b^2 )−90a^2 b^6 )/(9b^6 ))]  81a^3 b^9 y=ab(y^2 −10b^2 )(a^2 y^4 −10y^2 a^2 b^2 −90a^2 b^6 )                 =a^3 b(y^2 −10b^2 )(y^4 −10y^2 b^2 −90b^6 )                =a^3 b[y^6 −10y^4 b^2 −90y^2 b^6      −10b^2 y^4 +100b^4 y^2 +900b^8   =a^3 b[y^6 −20b^2 y^4 −(90b^6 −100b^4 )y^2 +900b^8 ]  =81a^3 b^9 y    ⇒81b^8 y=y^6 −20b^2 y^4 −10b^4 (9b^2 −10)y^2 +900b^8   ⇒y^6 −20b^2 [y^4 −(1/2)(9b^2 −10)b^2 y^2 +45b^6 ]−81b^8 y=0  =y^6 −20b^2 (y^2 −(((9b^2 −10)b^2 )/4))^2 −81b^8 y+45b^6 −(((9b^2 −10)b^4 )/(16))=0  ..........to continious

$$\begin{cases}{\mathrm{bx}^{\mathrm{3}} −\mathrm{10a}^{\mathrm{2}} \mathrm{bx}=\mathrm{3a}^{\mathrm{3}} \mathrm{y}\Rightarrow\:\:\:\boldsymbol{\mathrm{y}}=\frac{\boldsymbol{\mathrm{xb}}\left(\boldsymbol{\mathrm{x}}^{\mathrm{2}} −\mathrm{10}\boldsymbol{\mathrm{a}}^{\mathrm{2}} \right)}{\mathrm{3}\boldsymbol{\mathrm{a}}^{\mathrm{3}} }\:\left(\mathrm{1}\right)}\\{\mathrm{3b}^{\mathrm{3}} \mathrm{x}=\mathrm{ay}^{\mathrm{3}} −\mathrm{10ab}^{\mathrm{2}} \mathrm{y}\Rightarrow\:\:\boldsymbol{\mathrm{x}}=\frac{\boldsymbol{\mathrm{ya}}\left(\boldsymbol{\mathrm{y}}^{\mathrm{2}} −\mathrm{10}\boldsymbol{\mathrm{b}}^{\mathrm{2}} \right)}{\mathrm{3}\boldsymbol{\mathrm{b}}^{\mathrm{3}} }\:\:\left(\mathrm{2}\right)}\end{cases} \\ $$$$\boldsymbol{\mathrm{y}}^{\mathrm{2}} =\frac{\boldsymbol{\mathrm{x}}^{\mathrm{2}} \boldsymbol{\mathrm{b}}^{\mathrm{2}} \left(\boldsymbol{\mathrm{x}}^{\mathrm{2}} −\mathrm{10}\boldsymbol{\mathrm{a}}^{\mathrm{2}} \right)^{\mathrm{2}} }{\mathrm{9}\boldsymbol{\mathrm{a}}^{\mathrm{6}} } \\ $$$$\boldsymbol{\mathrm{x}}^{\mathrm{2}} =\frac{\boldsymbol{\mathrm{y}}^{\mathrm{2}} \boldsymbol{\mathrm{a}}^{\mathrm{2}} \left(\boldsymbol{\mathrm{y}}^{\mathrm{2}} −\mathrm{10}\boldsymbol{\mathrm{b}}^{\mathrm{2}} \right)}{\mathrm{9}\boldsymbol{\mathrm{b}}^{\mathrm{6}} } \\ $$$$\left(\mathrm{1}\right)\Leftrightarrow\boldsymbol{\mathrm{y}}=\frac{\boldsymbol{\mathrm{b}}}{\mathrm{3}\boldsymbol{\mathrm{a}}^{\mathrm{3}} }\left[\frac{\boldsymbol{\mathrm{ya}}\left(\boldsymbol{\mathrm{y}}^{\mathrm{2}} −\mathrm{10}\boldsymbol{\mathrm{b}}^{\mathrm{2}} \right.}{\mathrm{3}\boldsymbol{\mathrm{b}}^{\mathrm{3}} }\right]\left[\left(\frac{\boldsymbol{\mathrm{y}}^{\mathrm{2}} \boldsymbol{\mathrm{a}}^{\mathrm{2}} \left(\boldsymbol{\mathrm{y}}^{\mathrm{2}} −\mathrm{10}\boldsymbol{\mathrm{b}}^{\mathrm{2}} \right)−\mathrm{90}\boldsymbol{\mathrm{a}}^{\mathrm{2}} \boldsymbol{\mathrm{b}}^{\mathrm{6}} }{\mathrm{9}\boldsymbol{\mathrm{b}}^{\mathrm{6}} }\right]\right. \\ $$$$\mathrm{81}\boldsymbol{\mathrm{a}}^{\mathrm{3}} \boldsymbol{\mathrm{b}}^{\mathrm{9}} \boldsymbol{\mathrm{y}}=\boldsymbol{\mathrm{ab}}\left(\boldsymbol{\mathrm{y}}^{\mathrm{2}} −\mathrm{10}\boldsymbol{\mathrm{b}}^{\mathrm{2}} \right)\left(\boldsymbol{\mathrm{a}}^{\mathrm{2}} \boldsymbol{\mathrm{y}}^{\mathrm{4}} −\mathrm{10}\boldsymbol{\mathrm{y}}^{\mathrm{2}} \boldsymbol{\mathrm{a}}^{\mathrm{2}} \boldsymbol{\mathrm{b}}^{\mathrm{2}} −\mathrm{90}\boldsymbol{\mathrm{a}}^{\mathrm{2}} \boldsymbol{\mathrm{b}}^{\mathrm{6}} \right) \\ $$$$\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:=\boldsymbol{\mathrm{a}}^{\mathrm{3}} \boldsymbol{\mathrm{b}}\left(\boldsymbol{\mathrm{y}}^{\mathrm{2}} −\mathrm{10}\boldsymbol{\mathrm{b}}^{\mathrm{2}} \right)\left(\boldsymbol{\mathrm{y}}^{\mathrm{4}} −\mathrm{10}\boldsymbol{\mathrm{y}}^{\mathrm{2}} \boldsymbol{\mathrm{b}}^{\mathrm{2}} −\mathrm{90}\boldsymbol{\mathrm{b}}^{\mathrm{6}} \right) \\ $$$$\:\:\:\:\:\:\:\:\:\:\:\:\:\:=\boldsymbol{\mathrm{a}}^{\mathrm{3}} \boldsymbol{\mathrm{b}}\left[\boldsymbol{\mathrm{y}}^{\mathrm{6}} −\mathrm{10}\boldsymbol{\mathrm{y}}^{\mathrm{4}} \boldsymbol{\mathrm{b}}^{\mathrm{2}} −\mathrm{90}\boldsymbol{\mathrm{y}}^{\mathrm{2}} \boldsymbol{\mathrm{b}}^{\mathrm{6}} \right. \\ $$$$\:\:\:−\mathrm{10}\boldsymbol{\mathrm{b}}^{\mathrm{2}} \boldsymbol{\mathrm{y}}^{\mathrm{4}} +\mathrm{100}\boldsymbol{\mathrm{b}}^{\mathrm{4}} \boldsymbol{\mathrm{y}}^{\mathrm{2}} +\mathrm{900}\boldsymbol{\mathrm{b}}^{\mathrm{8}} \\ $$$$=\boldsymbol{\mathrm{a}}^{\mathrm{3}} \boldsymbol{\mathrm{b}}\left[\boldsymbol{\mathrm{y}}^{\mathrm{6}} −\mathrm{20}\boldsymbol{\mathrm{b}}^{\mathrm{2}} \boldsymbol{\mathrm{y}}^{\mathrm{4}} −\left(\mathrm{90}\boldsymbol{\mathrm{b}}^{\mathrm{6}} −\mathrm{100}\boldsymbol{\mathrm{b}}^{\mathrm{4}} \right)\boldsymbol{\mathrm{y}}^{\mathrm{2}} +\mathrm{900}\boldsymbol{\mathrm{b}}^{\mathrm{8}} \right] \\ $$$$=\mathrm{81}\boldsymbol{\mathrm{a}}^{\mathrm{3}} \boldsymbol{\mathrm{b}}^{\mathrm{9}} \boldsymbol{\mathrm{y}} \\ $$$$ \\ $$$$\Rightarrow\mathrm{81b}^{\mathrm{8}} \boldsymbol{\mathrm{y}}=\boldsymbol{\mathrm{y}}^{\mathrm{6}} −\mathrm{20}\boldsymbol{\mathrm{b}}^{\mathrm{2}} \boldsymbol{\mathrm{y}}^{\mathrm{4}} −\mathrm{10}\boldsymbol{\mathrm{b}}^{\mathrm{4}} \left(\mathrm{9}\boldsymbol{\mathrm{b}}^{\mathrm{2}} −\mathrm{10}\right)\boldsymbol{\mathrm{y}}^{\mathrm{2}} +\mathrm{900}\boldsymbol{\mathrm{b}}^{\mathrm{8}} \\ $$$$\Rightarrow\boldsymbol{\mathrm{y}}^{\mathrm{6}} −\mathrm{20}\boldsymbol{\mathrm{b}}^{\mathrm{2}} \left[\boldsymbol{\mathrm{y}}^{\mathrm{4}} −\frac{\mathrm{1}}{\mathrm{2}}\left(\mathrm{9}\boldsymbol{\mathrm{b}}^{\mathrm{2}} −\mathrm{10}\right)\boldsymbol{\mathrm{b}}^{\mathrm{2}} \boldsymbol{\mathrm{y}}^{\mathrm{2}} +\mathrm{45}\boldsymbol{\mathrm{b}}^{\mathrm{6}} \right]−\mathrm{81}\boldsymbol{\mathrm{b}}^{\mathrm{8}} \boldsymbol{\mathrm{y}}=\mathrm{0} \\ $$$$=\boldsymbol{\mathrm{y}}^{\mathrm{6}} −\mathrm{20}\boldsymbol{\mathrm{b}}^{\mathrm{2}} \left(\boldsymbol{\mathrm{y}}^{\mathrm{2}} −\frac{\left(\mathrm{9}\boldsymbol{\mathrm{b}}^{\mathrm{2}} −\mathrm{10}\right)\boldsymbol{\mathrm{b}}^{\mathrm{2}} }{\mathrm{4}}\right)^{\mathrm{2}} −\mathrm{81}\boldsymbol{\mathrm{b}}^{\mathrm{8}} \boldsymbol{\mathrm{y}}+\mathrm{45}\boldsymbol{\mathrm{b}}^{\mathrm{6}} −\frac{\left(\mathrm{9}\boldsymbol{\mathrm{b}}^{\mathrm{2}} −\mathrm{10}\right)\boldsymbol{\mathrm{b}}^{\mathrm{4}} }{\mathrm{16}}=\mathrm{0} \\ $$$$..........\boldsymbol{\mathrm{to}}\:\boldsymbol{\mathrm{continious}} \\ $$$$ \\ $$

Answered by Frix last updated on 01/Jun/23

bx^3 =10a^2 bx+3a^3 y ⇔ y=((bx(x^2 −10a^2 ))/(3a^3 ))  Inserting in the 2^(nd)  equation and factorizing  ((b^3 x(x^2 −a^2 )(x^2 −7a^2 )(x^2 −9a^2 )(x^2 −13a^2 ))/(27a^8 ))=0  The rest is easy

$${bx}^{\mathrm{3}} =\mathrm{10}{a}^{\mathrm{2}} {bx}+\mathrm{3}{a}^{\mathrm{3}} {y}\:\Leftrightarrow\:{y}=\frac{{bx}\left({x}^{\mathrm{2}} −\mathrm{10}{a}^{\mathrm{2}} \right)}{\mathrm{3}{a}^{\mathrm{3}} } \\ $$$$\mathrm{Inserting}\:\mathrm{in}\:\mathrm{the}\:\mathrm{2}^{\mathrm{nd}} \:\mathrm{equation}\:\mathrm{and}\:\mathrm{factorizing} \\ $$$$\frac{{b}^{\mathrm{3}} {x}\left({x}^{\mathrm{2}} −{a}^{\mathrm{2}} \right)\left({x}^{\mathrm{2}} −\mathrm{7}{a}^{\mathrm{2}} \right)\left({x}^{\mathrm{2}} −\mathrm{9}{a}^{\mathrm{2}} \right)\left({x}^{\mathrm{2}} −\mathrm{13}{a}^{\mathrm{2}} \right)}{\mathrm{27}{a}^{\mathrm{8}} }=\mathrm{0} \\ $$$$\mathrm{The}\:\mathrm{rest}\:\mathrm{is}\:\mathrm{easy} \\ $$

Commented by York12 last updated on 01/Jun/23

that would take a lot of time

$${that}\:{would}\:{take}\:{a}\:{lot}\:{of}\:{time} \\ $$$$ \\ $$

Commented by York12 last updated on 01/Jun/23

watch this

$${watch}\:{this} \\ $$

Answered by a.lgnaoui last updated on 01/Jun/23

(suite)     { ((bx^3 −10ba^2 x=3a^3 y   ⇒b=((3a^3 y)/(x(x^2 −10a^2 ))) (1))),((ay^3 −10ab^2 y=3b^3 x  ⇒a=((3b^3 x)/(y(y^2 −10b^2 )))  (2))) :}    Remarque:  ab=((3a^3 )/((x^2 −10a^2 )))×((3b^3 )/(y^2 −10b^2 ))      =((9a^3 b^3 )/((x^2 −10a^2 )(y^2 −10b^2 )))  ⇒9a^2 b^2 =(x^2 −10a^2 )(y^2 −10b^2 )  cette equation nous permet  de calculer    a en fonction  de b  et   y en fonxtion de x  9a^2 b^2 =x^2 y^2 −10b^2 x^2 −10a^2 y^2 +100a^2 b^2   91a^2 b^2 =10(a^2 y^2 +b^2 x^2 )−x^2 y^2         a^2 =((x^2 (10b^2 −y^2 ))/(91b^2 −10y^2 )) (si b≠y(√((10)/(91)))  etb>(y/( (√(10)))))

$$\left(\mathrm{suite}\right) \\ $$$$ \\ $$$$\begin{cases}{\mathrm{bx}^{\mathrm{3}} −\mathrm{10ba}^{\mathrm{2}} \mathrm{x}=\mathrm{3a}^{\mathrm{3}} \mathrm{y}\:\:\:\Rightarrow\boldsymbol{\mathrm{b}}=\frac{\mathrm{3}\boldsymbol{\mathrm{a}}^{\mathrm{3}} \mathrm{y}}{\mathrm{x}\left(\mathrm{x}^{\mathrm{2}} −\mathrm{10}\boldsymbol{\mathrm{a}}^{\mathrm{2}} \right)}\:\left(\mathrm{1}\right)}\\{\mathrm{ay}^{\mathrm{3}} −\mathrm{10ab}^{\mathrm{2}} \mathrm{y}=\mathrm{3b}^{\mathrm{3}} \mathrm{x}\:\:\Rightarrow\boldsymbol{\mathrm{a}}=\frac{\mathrm{3}\boldsymbol{\mathrm{b}}^{\mathrm{3}} \mathrm{x}}{\mathrm{y}\left(\mathrm{y}^{\mathrm{2}} −\mathrm{10b}^{\mathrm{2}} \right)}\:\:\left(\mathrm{2}\right)}\end{cases} \\ $$$$ \\ $$$$\boldsymbol{\mathrm{Remarque}}: \\ $$$$\mathrm{ab}=\frac{\mathrm{3a}^{\mathrm{3}} }{\left(\mathrm{x}^{\mathrm{2}} −\mathrm{10a}^{\mathrm{2}} \right)}×\frac{\mathrm{3b}^{\mathrm{3}} }{\mathrm{y}^{\mathrm{2}} −\mathrm{10b}^{\mathrm{2}} } \\ $$$$\:\:\:\:=\frac{\mathrm{9a}^{\mathrm{3}} \mathrm{b}^{\mathrm{3}} }{\left(\mathrm{x}^{\mathrm{2}} −\mathrm{10a}^{\mathrm{2}} \right)\left(\mathrm{y}^{\mathrm{2}} −\mathrm{10b}^{\mathrm{2}} \right)} \\ $$$$\Rightarrow\mathrm{9a}^{\mathrm{2}} \mathrm{b}^{\mathrm{2}} =\left(\mathrm{x}^{\mathrm{2}} −\mathrm{10a}^{\mathrm{2}} \right)\left(\mathrm{y}^{\mathrm{2}} −\mathrm{10b}^{\mathrm{2}} \right) \\ $$$$\mathrm{cette}\:\mathrm{equation}\:\mathrm{nous}\:\mathrm{permet}\:\:\mathrm{de}\:\mathrm{calculer} \\ $$$$\:\:\boldsymbol{\mathrm{a}}\:\mathrm{en}\:\mathrm{fonction}\:\:\mathrm{de}\:\boldsymbol{\mathrm{b}}\:\:\mathrm{et}\:\:\:\boldsymbol{\mathrm{y}}\:\mathrm{en}\:\mathrm{fonxtion}\:\mathrm{de}\:\boldsymbol{\mathrm{x}} \\ $$$$\mathrm{9}\boldsymbol{\mathrm{a}}^{\mathrm{2}} \boldsymbol{\mathrm{b}}^{\mathrm{2}} =\boldsymbol{\mathrm{x}}^{\mathrm{2}} \boldsymbol{\mathrm{y}}^{\mathrm{2}} −\mathrm{10}\boldsymbol{\mathrm{b}}^{\mathrm{2}} \boldsymbol{\mathrm{x}}^{\mathrm{2}} −\mathrm{10}\boldsymbol{\mathrm{a}}^{\mathrm{2}} \boldsymbol{\mathrm{y}}^{\mathrm{2}} +\mathrm{100}\boldsymbol{\mathrm{a}}^{\mathrm{2}} \boldsymbol{\mathrm{b}}^{\mathrm{2}} \\ $$$$\mathrm{91}\boldsymbol{\mathrm{a}}^{\mathrm{2}} \boldsymbol{\mathrm{b}}^{\mathrm{2}} =\mathrm{10}\left(\boldsymbol{\mathrm{a}}^{\mathrm{2}} \boldsymbol{\mathrm{y}}^{\mathrm{2}} +\boldsymbol{\mathrm{b}}^{\mathrm{2}} \boldsymbol{\mathrm{x}}^{\mathrm{2}} \right)−\boldsymbol{\mathrm{x}}^{\mathrm{2}} \boldsymbol{\mathrm{y}}^{\mathrm{2}} \\ $$$$ \\ $$$$\:\:\:\:\boldsymbol{\mathrm{a}}^{\mathrm{2}} =\frac{\boldsymbol{\mathrm{x}}^{\mathrm{2}} \left(\mathrm{10b}^{\mathrm{2}} −\boldsymbol{\mathrm{y}}^{\mathrm{2}} \right)}{\mathrm{91}\boldsymbol{\mathrm{b}}^{\mathrm{2}} −\mathrm{10}\boldsymbol{\mathrm{y}}^{\mathrm{2}} }\:\left(\boldsymbol{\mathrm{si}}\:\boldsymbol{\mathrm{b}}\neq\mathrm{y}\sqrt{\frac{\mathrm{10}}{\mathrm{91}}}\:\:\mathrm{etb}>\frac{\mathrm{y}}{\:\sqrt{\mathrm{10}}}\right)\: \\ $$$$ \\ $$

Answered by York12 last updated on 01/Jun/23

bx^3  = 10a^2 bx + 3a^3 y ........(i)  ay^3  = 10ab^2 y + 3b^3 x  .......(ii)  (((i))/((ii))) we obtain : ((bx^3 )/(ay^3 ))=((a^2 (10bx + 3ay))/(b^2 (10ay + 3bx)))   ⇒ ((b^3 x^3 )/(a^3 y^3 ))= ((10bx + 3ay)/(10ay +3bx)) = ((((10 bx)/(ay))+3)/(10 + ((3 bx)/(ay))))   set ((bx)/(ay)) = λ ⇒ λ^3  = ((10 λ +3)/(10 + 3 λ)) ⇒ 3λ^4  + 10 λ^(3 )  = 10λ +3   3λ^4  − 3 + 10 λ^3  −10 λ = 0  (λ^2  −1)(3λ^2  + 3) + 10 λ (λ^2  −1)=0  (λ−1)(λ+1)(λ+3)(3λ+1) =0   ⇒ λ ∈ { 1 , −1 , −3 , ((−1)/3) }  By substituting we obtain The required   values of x , y , a and b .★

$${bx}^{\mathrm{3}} \:=\:\mathrm{10}{a}^{\mathrm{2}} {bx}\:+\:\mathrm{3}{a}^{\mathrm{3}} {y}\:........\left({i}\right) \\ $$$${ay}^{\mathrm{3}} \:=\:\mathrm{10}{ab}^{\mathrm{2}} {y}\:+\:\mathrm{3}{b}^{\mathrm{3}} {x}\:\:.......\left({ii}\right) \\ $$$$\frac{\left({i}\right)}{\left({ii}\right)}\:{we}\:{obtain}\::\:\frac{{bx}^{\mathrm{3}} }{{ay}^{\mathrm{3}} }=\frac{{a}^{\mathrm{2}} \left(\mathrm{10}{bx}\:+\:\mathrm{3}{ay}\right)}{{b}^{\mathrm{2}} \left(\mathrm{10}{ay}\:+\:\mathrm{3}{bx}\right)}\: \\ $$$$\Rightarrow\:\frac{{b}^{\mathrm{3}} {x}^{\mathrm{3}} }{{a}^{\mathrm{3}} {y}^{\mathrm{3}} }=\:\frac{\mathrm{10}{bx}\:+\:\mathrm{3}{ay}}{\mathrm{10}{ay}\:+\mathrm{3}{bx}}\:=\:\frac{\frac{\mathrm{10}\:{bx}}{{ay}}+\mathrm{3}}{\mathrm{10}\:+\:\frac{\mathrm{3}\:{bx}}{{ay}}}\: \\ $$$${set}\:\frac{{bx}}{{ay}}\:=\:\lambda\:\Rightarrow\:\lambda^{\mathrm{3}} \:=\:\frac{\mathrm{10}\:\lambda\:+\mathrm{3}}{\mathrm{10}\:+\:\mathrm{3}\:\lambda}\:\Rightarrow\:\mathrm{3}\lambda^{\mathrm{4}} \:+\:\mathrm{10}\:\lambda^{\mathrm{3}\:} \:=\:\mathrm{10}\lambda\:+\mathrm{3}\: \\ $$$$\mathrm{3}\lambda^{\mathrm{4}} \:−\:\mathrm{3}\:+\:\mathrm{10}\:\lambda^{\mathrm{3}} \:−\mathrm{10}\:\lambda\:=\:\mathrm{0} \\ $$$$\left(\lambda^{\mathrm{2}} \:−\mathrm{1}\right)\left(\mathrm{3}\lambda^{\mathrm{2}} \:+\:\mathrm{3}\right)\:+\:\mathrm{10}\:\lambda\:\left(\lambda^{\mathrm{2}} \:−\mathrm{1}\right)=\mathrm{0} \\ $$$$\left(\lambda−\mathrm{1}\right)\left(\lambda+\mathrm{1}\right)\left(\lambda+\mathrm{3}\right)\left(\mathrm{3}\lambda+\mathrm{1}\right)\:=\mathrm{0}\: \\ $$$$\Rightarrow\:\lambda\:\in\:\left\{\:\mathrm{1}\:,\:−\mathrm{1}\:,\:−\mathrm{3}\:,\:\frac{−\mathrm{1}}{\mathrm{3}}\:\right\} \\ $$$${By}\:{substituting}\:{we}\:{obtain}\:{The}\:{required}\: \\ $$$${values}\:{of}\:{x}\:,\:{y}\:,\:{a}\:{and}\:{b}\:.\bigstar \\ $$$$ \\ $$

Commented by Frix last updated on 01/Jun/23

To divide 2 equations is not allowed:  (1) 6=4 false  (2) 3=2 false  (((1))/((2))) (6/3)=(4/2) true

$$\mathrm{To}\:\mathrm{divide}\:\mathrm{2}\:\mathrm{equations}\:\mathrm{is}\:\mathrm{not}\:\mathrm{allowed}: \\ $$$$\left(\mathrm{1}\right)\:\mathrm{6}=\mathrm{4}\:\mathrm{false} \\ $$$$\left(\mathrm{2}\right)\:\mathrm{3}=\mathrm{2}\:\mathrm{false} \\ $$$$\frac{\left(\mathrm{1}\right)}{\left(\mathrm{2}\right)}\:\frac{\mathrm{6}}{\mathrm{3}}=\frac{\mathrm{4}}{\mathrm{2}}\:\mathrm{true} \\ $$

Commented by ajfour last updated on 01/Jun/23

but  if      6=8−2                      3=13−10  ⇒  2=(6/3)=((8−2)/(13−10))     (..)!

$${but}\:\:{if}\:\:\:\:\:\:\mathrm{6}=\mathrm{8}−\mathrm{2} \\ $$$$\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\mathrm{3}=\mathrm{13}−\mathrm{10} \\ $$$$\Rightarrow\:\:\mathrm{2}=\frac{\mathrm{6}}{\mathrm{3}}=\frac{\mathrm{8}−\mathrm{2}}{\mathrm{13}−\mathrm{10}}\:\:\:\:\:\left(..\right)! \\ $$

Commented by York12 last updated on 01/Jun/23

what you have written here is based on if   6=4 is false   3=2 is false   but if the statement is true then we can always   divide two equations

$${what}\:{you}\:{have}\:{written}\:{here}\:{is}\:{based}\:{on}\:{if}\: \\ $$$$\mathrm{6}=\mathrm{4}\:{is}\:{false}\: \\ $$$$\mathrm{3}=\mathrm{2}\:{is}\:{false}\: \\ $$$${but}\:{if}\:{the}\:{statement}\:{is}\:{true}\:{then}\:{we}\:{can}\:{always}\: \\ $$$${divide}\:{two}\:{equations}\: \\ $$

Commented by York12 last updated on 01/Jun/23

nothing extraordinary

$${nothing}\:{extraordinary} \\ $$

Commented by York12 last updated on 01/Jun/23

  To divide 2 equations is not allowed:  (1) 6=4 false  (2) 3=2 false  (((1))/((2))) (6/3)=(4/2) true  whereas in my questions the equations   are right then  ((LHS_(equ (1)) )/(LHS_(equ(2)) )) =((RHS_(equ (1)) )/(RHS_(equ (2)) ))

$$ \\ $$$$\mathrm{To}\:\mathrm{divide}\:\mathrm{2}\:\mathrm{equations}\:\mathrm{is}\:\mathrm{not}\:\mathrm{allowed}: \\ $$$$\left(\mathrm{1}\right)\:\mathrm{6}=\mathrm{4}\:\mathrm{false} \\ $$$$\left(\mathrm{2}\right)\:\mathrm{3}=\mathrm{2}\:\mathrm{false} \\ $$$$\frac{\left(\mathrm{1}\right)}{\left(\mathrm{2}\right)}\:\frac{\mathrm{6}}{\mathrm{3}}=\frac{\mathrm{4}}{\mathrm{2}}\:\mathrm{true} \\ $$$${whereas}\:{in}\:{my}\:{questions}\:{the}\:{equations}\: \\ $$$${are}\:{right}\:{then} \\ $$$$\frac{{LHS}_{{equ}\:\left(\mathrm{1}\right)} }{{LHS}_{{equ}\left(\mathrm{2}\right)} }\:=\frac{{RHS}_{{equ}\:\left(\mathrm{1}\right)} }{{RHS}_{{equ}\:\left(\mathrm{2}\right)} } \\ $$$$ \\ $$

Commented by Frix last updated on 01/Jun/23

You′re wrong here.  Another example (we had some similar  “solutions” here some time ago):  (1) x^4 −x^3 −43x^2 +23x+203=0  (2) x^3 −6x^2 −13x+41=0  =================  (1) x^4 −x^3 −43x^2 −23x+210=7  (2) x^3 −6x^2 −13x+42=1  =================  (1) (x−7)(x−2)(x+3)(x+5)=7  (2) (x−7)(x−2)(x+3)=1  =================  (((1))/((2))) x+5=7 ⇒ x=2 (false)    But both equations are “true”...

$$\mathrm{You}'\mathrm{re}\:\mathrm{wrong}\:\mathrm{here}. \\ $$$$\mathrm{Another}\:\mathrm{example}\:\left(\mathrm{we}\:\mathrm{had}\:\mathrm{some}\:\mathrm{similar}\right. \\ $$$$\left.``\mathrm{solutions}''\:\mathrm{here}\:\mathrm{some}\:\mathrm{time}\:\mathrm{ago}\right): \\ $$$$\left(\mathrm{1}\right)\:{x}^{\mathrm{4}} −{x}^{\mathrm{3}} −\mathrm{43}{x}^{\mathrm{2}} +\mathrm{23}{x}+\mathrm{203}=\mathrm{0} \\ $$$$\left(\mathrm{2}\right)\:{x}^{\mathrm{3}} −\mathrm{6}{x}^{\mathrm{2}} −\mathrm{13}{x}+\mathrm{41}=\mathrm{0} \\ $$$$================= \\ $$$$\left(\mathrm{1}\right)\:{x}^{\mathrm{4}} −{x}^{\mathrm{3}} −\mathrm{43}{x}^{\mathrm{2}} −\mathrm{23}{x}+\mathrm{210}=\mathrm{7} \\ $$$$\left(\mathrm{2}\right)\:{x}^{\mathrm{3}} −\mathrm{6}{x}^{\mathrm{2}} −\mathrm{13}{x}+\mathrm{42}=\mathrm{1} \\ $$$$================= \\ $$$$\left(\mathrm{1}\right)\:\left({x}−\mathrm{7}\right)\left({x}−\mathrm{2}\right)\left({x}+\mathrm{3}\right)\left({x}+\mathrm{5}\right)=\mathrm{7} \\ $$$$\left(\mathrm{2}\right)\:\left({x}−\mathrm{7}\right)\left({x}−\mathrm{2}\right)\left({x}+\mathrm{3}\right)=\mathrm{1} \\ $$$$================= \\ $$$$\frac{\left(\mathrm{1}\right)}{\left(\mathrm{2}\right)}\:{x}+\mathrm{5}=\mathrm{7}\:\Rightarrow\:{x}=\mathrm{2}\:\left(\mathrm{false}\right) \\ $$$$ \\ $$$$\mathrm{But}\:\mathrm{both}\:\mathrm{equations}\:\mathrm{are}\:``\mathrm{true}''... \\ $$

Commented by ajfour last updated on 02/Jun/23

coz   if x=2   we  shudnt have  divided by (x−7)(x−2)(x+3)  so it doesnt  deceive. we know  x=2  is then false.

$${coz}\:\:\:{if}\:{x}=\mathrm{2}\:\:\:{we}\:\:{shudnt}\:{have} \\ $$$${divided}\:{by}\:\left({x}−\mathrm{7}\right)\left({x}−\mathrm{2}\right)\left({x}+\mathrm{3}\right) \\ $$$${so}\:{it}\:{doesnt}\:\:{deceive}.\:{we}\:{know} \\ $$$${x}=\mathrm{2}\:\:{is}\:{then}\:{false}. \\ $$

Commented by York12 last updated on 02/Jun/23

sorry but for again you are wrong   because both equations canot be true   simultaously  (x−7)(x−2)(x+3)_(T) =1  (x−7)(x−2)(x+3)_(T) (x+5)=7  T =1   T × (x+5) =7 → x=2  That is so trivial   but if you will substitute you will   find that x doesnot satisfy the given  system of equations  then that means there are two variables  to make that happen your equations  has to written as   (y−7)(y−2)(y+3)(x+5)=7  (y−7)(y−2)(y+3)=1  then that can happen    and since you have commited  such a mistake I advise you  to study theory of equations  specificly the concept of common roots  cause those two equations that you have   obtained doesnot have any common   roots

$${sorry}\:{but}\:{for}\:{again}\:{you}\:{are}\:{wrong}\: \\ $$$${because}\:{both}\:{equations}\:{canot}\:{be}\:{true}\: \\ $$$${simultaously} \\ $$$$\underset{{T}} {\underbrace{\left({x}−\mathrm{7}\right)\left({x}−\mathrm{2}\right)\left({x}+\mathrm{3}\right)}}=\mathrm{1} \\ $$$$\underset{{T}} {\underbrace{\left({x}−\mathrm{7}\right)\left({x}−\mathrm{2}\right)\left({x}+\mathrm{3}\right)}}\left({x}+\mathrm{5}\right)=\mathrm{7} \\ $$$${T}\:=\mathrm{1}\: \\ $$$${T}\:×\:\left({x}+\mathrm{5}\right)\:=\mathrm{7}\:\rightarrow\:{x}=\mathrm{2} \\ $$$${That}\:{is}\:{so}\:{trivial}\: \\ $$$${but}\:{if}\:{you}\:{will}\:{substitute}\:{you}\:{will}\: \\ $$$${find}\:{that}\:{x}\:{doesnot}\:{satisfy}\:{the}\:{given} \\ $$$${system}\:{of}\:{equations} \\ $$$${then}\:{that}\:{means}\:{there}\:{are}\:{two}\:{variables} \\ $$$${to}\:{make}\:{that}\:{happen}\:{your}\:{equations} \\ $$$${has}\:{to}\:{written}\:{as}\: \\ $$$$\left({y}−\mathrm{7}\right)\left({y}−\mathrm{2}\right)\left({y}+\mathrm{3}\right)\left({x}+\mathrm{5}\right)=\mathrm{7} \\ $$$$\left({y}−\mathrm{7}\right)\left({y}−\mathrm{2}\right)\left({y}+\mathrm{3}\right)=\mathrm{1} \\ $$$${then}\:{that}\:{can}\:{happen}\:\: \\ $$$${and}\:{since}\:{you}\:{have}\:{commited} \\ $$$${such}\:{a}\:{mistake}\:{I}\:{advise}\:{you} \\ $$$${to}\:{study}\:{theory}\:{of}\:{equations} \\ $$$${specificly}\:{the}\:{concept}\:{of}\:{common}\:{roots} \\ $$$${cause}\:{those}\:{two}\:{equations}\:{that}\:{you}\:{have}\: \\ $$$${obtained}\:{doesnot}\:{have}\:{any}\:{common}\: \\ $$$${roots} \\ $$$$ \\ $$$$ \\ $$$$ \\ $$$$ \\ $$

Commented by York12 last updated on 02/Jun/23

wrong  cause both equtions can not be true   cause they do not have any common roots !!!!    then for again the assumptions  are wrong

$${wrong} \\ $$$${cause}\:{both}\:{equtions}\:{can}\:{not}\:{be}\:{true}\: \\ $$$${cause}\:{they}\:{do}\:{not}\:{have}\:{any}\:{common}\:{roots}\:!!!! \\ $$$$ \\ $$$${then}\:{for}\:{again}\:{the}\:{assumptions} \\ $$$${are}\:{wrong}\: \\ $$$$ \\ $$

Commented by ajfour last updated on 02/Jun/23

who do u exactly tell?this all..

$${who}\:{do}\:{u}\:{exactly}\:{tell}?{this}\:{all}.. \\ $$

Commented by York12 last updated on 02/Jun/23

to frix

$${to}\:{frix} \\ $$

Commented by ajfour last updated on 03/Jun/23

He's long past all this, we ll never get over!

Commented by Frix last updated on 08/Jun/23

I′m not an idiot.  You cannot divide 2 equations before  showing that this division is legit.

$$\mathrm{I}'\mathrm{m}\:\mathrm{not}\:\mathrm{an}\:\mathrm{idiot}. \\ $$$$\mathrm{You}\:\mathrm{cannot}\:\mathrm{divide}\:\mathrm{2}\:\mathrm{equations}\:{before} \\ $$$$\mathrm{showing}\:\mathrm{that}\:\mathrm{this}\:\mathrm{division}\:\mathrm{is}\:\mathrm{legit}. \\ $$

Commented by York12 last updated on 13/Jun/23

no you can

$${no}\:{you}\:{can} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com